2019
DOI: 10.1063/1.5054166
|View full text |Cite
|
Sign up to set email alerts
|

Silicon surface passivation by transparent conductive zinc oxide

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 46 publications
5
41
1
Order By: Relevance
“…This hypothesis is supported by the fact that the passivation quality of PO x /Al 2 O 3 stacks without SiN x capping layer does not improve but rather degrades after firing ( J 0 can increase by ≈20 fA cm −2 ). Such loss of passivation upon annealing or firing is often attributed to effusion of hydrogen from the film and interface and comparable cases have been reported for Al 2 O 3 [ 7 ] as well as poly‐Si [ 21 ] and ZnO [ 22 ] with and without capping layer. In addition, when depositing the SiN x layer, an increase in J 0 of ≈20–40 fA cm −2 can be observed, which can be largely repaired by the firing treatment, thus explaining the difference in J 0 for the planar samples without and with SiN x capping layer and firing treatment, as shown in Figure 2a,b, respectively.…”
Section: Figuresupporting
confidence: 55%
“…This hypothesis is supported by the fact that the passivation quality of PO x /Al 2 O 3 stacks without SiN x capping layer does not improve but rather degrades after firing ( J 0 can increase by ≈20 fA cm −2 ). Such loss of passivation upon annealing or firing is often attributed to effusion of hydrogen from the film and interface and comparable cases have been reported for Al 2 O 3 [ 7 ] as well as poly‐Si [ 21 ] and ZnO [ 22 ] with and without capping layer. In addition, when depositing the SiN x layer, an increase in J 0 of ≈20–40 fA cm −2 can be observed, which can be largely repaired by the firing treatment, thus explaining the difference in J 0 for the planar samples without and with SiN x capping layer and firing treatment, as shown in Figure 2a,b, respectively.…”
Section: Figuresupporting
confidence: 55%
“…This loss of passivation is most likely related to roughening of the Si/ SiO 2 /ZnO interface, as will be discussed later on in this work in the section on TEM imaging of the contact structure. Another plausible contributor to the loss of passivation is effusion of hydrogen, as thermal effusion measurements in our previous work on the passivation by ZnO/ Al 2 O 3 stacks indeed showed the effusion of H 2 at temperatures above 400-450 o C and even effusion of H 2 O at temperatures exceeding approximately 600 o C [49]. The loss of hydrogen can however not be the sole mechanism, as can be inferred from the fact that SiO 2 /poly-Si/ALD Al 2 O 3 contacts, examined in our previous work, are thermally stable up to temperatures 600 o C for identical ALD Al 2 O 3 thickness and FGA ambient [48].…”
Section: Resultsmentioning
confidence: 91%
“…% was estimated to be 0.4, 0.8, 1.7 and 2.6%, respectively. For the passivation studies and contact resistivity measurements a ZnO(:Al) thickness of 20 nm was used, since our previous work showed that equally good passivation can be obtained for films as thin as 13 nm as for the device-relevant thickness of approximately 75 nm [49]. For type D samples the ZnO(:Al) films had a thickness of 75-85 nm since the optoelectronic quality of TCOs typically increases with film thickness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a significant amount of Al has diffused into the native oxide, which remains amorphous but with a composition Si 0.5 Al 0.5 O 2 . It is worth noting that most films deposited by ALD do exhibit a thin silicon dioxide layer sandwiched between the silicon substrate and thin film, [28][29][30][31] even when the dielectric being deposited does not use an oxygen containing precursor or co-reactant. An example of this can be seen in the ESI (Fig.…”
Section: Nanoscale Papermentioning
confidence: 99%